PERENCANAAN STRATEGI PRIORITAS KESEMPATAN KERJA DI KOTA DENPASAR - Nila Indriana Putri; Wahyu Hidayat; M Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2017)
The current economic development concerns the number of job opportunities that a region can provide. In accordance with Nuraini and Suliswanto (2014) research that Indonesia is currently experiencing demographic bonus where the proportion of productive population is very big, it means the number of workforce in Indonesia is also bigger. The purpose of this study is to know the sector of employment opportunity base is also the strategy used for the expansion of employment opportunities in the city of Denpasar. The method used is Location Question (LQ). Shift-share, and SWOT analysis. The research data is taken from BAdan Publication and Statistics Center of Denpasar and Bali Province for the period of 2011-2015 and also distributed questionnaires to 24 respondents in Denpasar Office of Manpower Office. Result of research indicate that occupation base sector of job opportunity in Denpasar highest is transportation sector, warehousing and communication with amount of calculation 1.70, while employment expansion strategy of Denpasar city is at point (1.96, 1.31) quadrant I which mean strategy lead to maintain power factor and the opportunity of Denpasar City with priority strategy is government policy for creative society empowerment.Keywords: Economic Development, Employment Opportunity, Base Sector, Strategy